(untitled) (Revista Iberoamericana de Bioética, 2017)
Vulnerability in bioethics is usually understood from the individual perspective, due in part to the way health is conceived under the biomedical model. The ethics of public health lead to an understanding of vulnerability from the social perspective, as they incorporate some characteristics of public health, such as prevention or avoidance of damage in situations of domination or dependence. Awareness of social vulnerability in research can help to avoid abuse due to lack of autonomy in individuals.